Trying out new cafes in town: assessing the impact of physical environment on visit intention / Chong Ka Leong - Chong, Ka Leong (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2018)
In the face of substantial investments in café physical environment set-up, café's owners and managers are giving little indication concerning their expensive set-up of a café's overall effectiveness in driving consumer visit intention. This study hypothesized the new customers' visit intention to a newly set-up café could be predicted by four physical environment factors: facility aesthetics, ambience, lighting, and spatial arrangement. Online survey questionnaires were distributed to 200 respondents using convenience purposive sampling approach, and Structural Equation Modelling (SEM) was implemented to examine the hypothesized relationships. While facility aesthetics and lighting in their current form do offer some "pull-factor" building benefits, their effect on visit intention is significantly stronger than ambience and spatial arrangement within a café. Thus, the investment of café physical environment does deliver some advantage, but conceivably not in the way the owners and managers desires. The café owners and managers should consider the importance of facility aesthetics and lighting in café layout and engineering design rather than overly focus on ambience creation and space arrangement.